Inter-organizational Knowledge Sharing in the Context of Game Theory - Alina CZAPLA (Communications of International Proceedings, 2021)
Knowledge management and especially knowledge sharing (KS) are currently the focus of researchers and businessmen. The emphasis is mainly on KS within the organization, but more and more researchers are paying attention to the importance of inter-organizational knowledge sharing (IKS). Knowledge is a valuable resource today, so organizations face a strategic decision - to share or not to share it. Game theory can help in solving this dilemma because it uses economic and mathematical tools to solve decision-making problems (Geckil and Anderson, 2010). The purpose of this article is to develop a decision path for two organizations, that face the choice of mutual KS. Possibilities for its implementation are also considered.
Keywords: knowledge sharing; inter-organizational knowledge sharing; decision path; game theory.